Efficient Synthesis of Macromolecular DO3A@Gn Derivatives for Potential Application in MRI Diagnostics: From Polymer Conjugates to Polymer Nanoparticles. Issue 1 (18th September 2022) - Kampmann, Anne‐Larissa; Hiller, Wolf; Weberskirch, Ralf
Abstract: Herein, the synthesis of three different macromolecular DO3A@Gn conjugates based on poly(2‐oxazoline)s is presented. Therefore, poly(2‐methyl‐2‐oxazoline) is synthesized by a ring‐opening, cationic polymerization and the polymerization is terminated with DO3A( t Bu)3 . The best results are obtained after 48 h at 120 °C with degree of termination of 86%. After deprotection of the DO3A ligand and complexation with Gn 3+, relaxivity as measured with a magnetic field strength of 9.4 T (400 MHz) reveals values for r1 of up to 2.32 mm −1 s −1 . The concept is extended to a block copolymer based on 2‐heptyl‐2‐oxazoline and 2‐methyl‐2‐oxazoline that is again terminated with DO3A( t Bu)3 to form micelles with a size of 12.6 ± 0.7 nm after DO3A( t Bu)3 termination and deprotection of the 1, 4, 7, 10‐tetraazacyclododecane‐ N, N, N, N ‐tetraacetic acid ligand. After complexation with Gn 3+, relaxivity r1 is 10.1 mm −1 s −1 as determined from the slope of the plot of 1/T1 against the gadolinium(III) concentration at 9.4 T. Finally, crosslinked nanoparticles are prepared from amphiphilic macro‐monomers that form micelles in water and are crosslinked throughout the core in the presence of azoisobutyronitrile (AIBN). The nanoparticle is 32.9 ± 7.8 nm in size after Gn 3+ complexation and reveals a relaxivity r1 of 6.77 mm −1 s −1 . Abstract : Herein, poly(2‐oxazoline) homo‐ and copolymers are used for functionalization with the 1, 4, 7, 10‐tetraazacyclododecane‐ N, N, N, N ‐tetraacetic acid chelator and subsequent complexation with Gn(III). The resulting conjugates are utilized for micelle and nanoparticle formation and are further analyzed and compared toward their relaxivity as a prerequisite for their possible application in magnetic resonance imaging diagnostics.